1984
DOI: 10.1093/oxfordjournals.eurheartj.a061694
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of two dimensional echocardiography in detection of impaired left ventricular function

Abstract: The purpose of the study was to determine the sensitivity and specificity of two-dimensional echocardiography (2dE) in the detection of impaired left ventricular function, compared with cineventriculography (CVG). Apical two-dimensional echocardiograms were performed in 110 patients undergoing heart catheterization for the evaluation of clinically suspected coronary heart disease (50 patients), valvular heart disease (38 patients) and congestive cardiomyopathy (22 patients). The left ventricle was scanned in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
3

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 0 publications
0
6
0
3
Order By: Relevance
“…Medical literature review showed the range of sensitivity and specificity for echocardiography to be 75%-94% and 90%-100%, respectively, when radionuclide angiography is the reference standard (13-18) (Table 1; Appendix 1). Thus, we used conservative values of 75% for sensitivity and 90% for specificity.…”
Section: Methodsmentioning
confidence: 99%
“…Medical literature review showed the range of sensitivity and specificity for echocardiography to be 75%-94% and 90%-100%, respectively, when radionuclide angiography is the reference standard (13-18) (Table 1; Appendix 1). Thus, we used conservative values of 75% for sensitivity and 90% for specificity.…”
Section: Methodsmentioning
confidence: 99%
“…Para el diagnóstico de DM se tomaron en cuenta los criterios de la American Diabetes Association del 2009 (7) , el tiempo de diagnóstico se registró en años. Se realizaron ecocardiografías en modo bidimensional (sensibilidad del 85%, especificidad del 97%, valor predictivo positivo del 98% y valor predictivo negativo del 94%) (8,9) , las cuales fueron realizadas por un cardiólogo con formación especializada en ecocardiografía. Para medir la masa ventricular se empleó las fórmulas validadas por la Sociedad Americana de Ecocardiografía, el diagnóstico de HVI se realizó en base al índice de masa ventricular izquierdo (IMVi), el cual se calcula dividiendo la masa ventricular izquierda entre la superficie corporal total; se consideró HVI en quienes presentaban un IMVi mayor a 95 g/m 2 en mujeres y mayor a 115 g/m 2 en varones (10) .…”
Section: El Estudiounclassified
“…Mathematisch hat sie aber keine Beziehung zur Simpson-Regel, die besagt, dass das Volumen eines Rotationsellipsoids durch die Aufsummierung von Trapezoiden berechnet wird, deren Volumen durch Addition gerader und ungerader Deck-und Bodenplatten, zur Bestimmung des mittleren Durchmessers des Trapezoids und der Trapezoidhöhe, analysiert wird. Wesentlich ungenauer sind und deshalb nicht benutzt werden sollten die Flächen-Längen und die Ellipsoid-Methode, da hier nur sehr ungenügende Ansätze zur Erfassung des Volumens des Rotationsellipsoids, vor allem bei regionalen Wandbewegungsstörungen, vorliegen.Für die Enddiastole und Endsystole sind Normwerte sowohl für Männer als auch Frauen bezogen auf die Körperoberfläche berechnet worden, die bei der Austestung eine sehr hohe Sensitivität und Spezifität aufweisen [4][5][6]. Berücksichtigt werden muss noch die Herzfrequenz, da pro 10 Schläge/min das EDV um 4 ml, das ESV um 2 ml und die EF um 1% in Abhängigkeit…”
unclassified
“…Für die Enddiastole und Endsystole sind Normwerte sowohl für Männer als auch Frauen bezogen auf die Körperoberfläche berechnet worden, die bei der Austestung eine sehr hohe Sensitivität und Spezifität aufweisen [4][5][6]. Berücksichtigt werden muss noch die Herzfrequenz, da pro 10 Schläge/min das EDV um 4 ml, das ESV um 2 ml und die EF um 1% in Abhängigkeit…”
unclassified